Perbandingan Morfometrik Sistem Pencernaan Ikan Lele (Clarias batrachus), Ikan Nila (Oreochromis niloticus), dan Ikan Kembung (Rastrelliger sp.) - Malini, Desak Made; Putri, Deviana Aulia; Setiawati, Tia (LPPM Universitas Terbuka, 2024)
Fish have a diversity of habitats and the types of food they consume, resulting in differences between species, especially in the morphology and morphometrics of their internal organs. One part of the fish that has significant differences is the digestive system. These differences allow fish to optimize their digestion to suit environmental conditions and the type of food they consume, thus ensuring better survival and reproduction. The aim of the study was to compare morphometrics in the digestive system organs of catfish (Clarias batrachus), tilapia (Oreochromis niloticus), and mackerel (Rastrelliger sp.). The research stages included sampling, anatomical preparation of fish, measurement of weight and length of digestive organs, measurement of Gastro Somatic Index (GaSI), measurement of Intestine Somatic Index (ISI), measurement of Gut Lengths (RGL), measurement of Relative Intestine Lengths (RIL), and measurement of Hepatosomatic Index (HSI). Analysis used one-way variance (oneway Anova) utilizing Statistical Package for the Social Sciences (SPSS) 22 software and Duncan's multiple range test. The results showed that GaSI, RGL, RIL, and HSI values of the three fish species were significantly different, while ISI values were not significantly different. It was concluded that there were morphometric differences in the digestive system organs of tilapia, mackerel, and catfish.